A critical study of Birgivi Mehmed Efendi’s (d.981/1573) works and their dissemination in manuscript form - Kaylı, Ahmet. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This study examines how one of the most influential and controversial Ottoman scholars of all time, Birgivi Mehmed Efendi (929-981 / 1523-1573), was perceived and received by other Ottoman readers and writers in the centuries following his death. This it accomplishes through a critical analysis of his bibliography on the one hand, and through a study of the historical dissemination of his works on the other. By critically handling the over one-hundred texts that had been attributed to Birgivi, the study identifies many misattributions to him and illustrates that some of these false attributions were directly instrumental in turning Birgivi into an anti-Sufi scholar with an uncompromising selefî persuasion, an image that is still well and alive, if also increasingly questioned, in the present time. The thesis also scrutinizes the inventory of Birgivi’s own works in order to establish as accurately as possible the relative significance of each work and the role that each might have played in the formation of the image of the author as well as in the determination of his reception. Finally, by exploring the dissemination of manuscript copies of these works based on the manuscript libraries in Istanbul, the study first proposes a historical map of Birgivi’s works in the seventeenth and eighteenth centuries, and then tries to understand and explain the dissemination in the historical context and in relation to the developments of the period.